Different siderophores contribute to the high-pathogenicity phenotype in Yersinia - A. Rakin; D. Garzetti (Проблемы особо опасных инфекций, 2013)
capture and transport in bacteria. At least one endogenous siderophore system, yersiniabactin, is known to be involved in iron acquisition in highly virulent Yersiniae . Its inactivation in Y. pestis and Y. enterocolitica subsp. enterocolitica results in significant attenuation of virulence. However, the yersiniabactin is not present in all highly virulent Yersiniae. Indeed, the large group of Y. pseudotuberculosis serotypes O2, O3, O4, O5 as well as serotype O1 Far East Scarlet like fever (FESLF) strains carry an alternative, iron acquisition system, pseudochelin, encoded by the Yersinia non-ribosomal peptide ynp locus. Thus, the yersiniabactin activity is not the only one associated with the high-pathogenicity phenotype of the human pathogenic Yersiniae .